Stepwise Diagnostic Evaluation in Pediatric Epilepsy: Clinical and EEG Predictors of MRI Positivity and Diagnostic Reclassification - Aytaç, Adil; Akay, Emrah; Dokurel Çetin, Professor İpek; Bulut, Mert; Yanik Keyik, Bahar; Bülbül, Erdoğan; Demirpolat, Gülen (The European Research Journal, 2026)
Objective: This study aimed to evaluate the predictive value of clinical and electroencephalographic (EEG) findings for identifying epileptogenic structural lesions on cranial magnetic resonance imaging (MRI) in pediatric epilepsy, and to assess the contribution of MRI to diagnostic reclassification.Methods: A total of 207 pediatric patients with a confirmed diagnosis of epilepsy were retrospectively analyzed. The diagnostic workflow was evaluated through a stepwise model integrating clinical assessment, EEG, and MRI. The primary endpoints comprised the MRI positivity rate, defined by the detection of epileptogenic structural lesions, and the diagnostic reclassification rate, defined as any modification in epilepsy type classification or etiological category following the incorporation of EEG and/or MRI findings. Independent predictors of MRI positivity were identified using multivariable logistic regression analysis.Results: Epileptogenic structural lesions were identified in 9.7% of patients. Despite a relatively modest MRI positivity rate, imaging significantly contributed to diagnostic refinement. Among cases with normal EEG findings, MRI revealed structural pathology in 12%. The overall diagnostic reclassification rate following the addition of MRI was 9.7%. In multivariable analysis, focal-onset seizures (OR=2.63), developmental delay (OR=2.91), abnormal neurological examination (OR=3.08), and focal epileptiform EEG activity (OR=2.47) emerged as independent predictors of MRI positivity (all P